Hierarchical Activated Carbon Fibers as a Sustainable Electrode and Natural Seawater as a Sustainable Electrolyte for High‐Performance Supercapacitor. Issue 9 (21st June 2020) - Challagulla, Navakanth Vijay; Vijayakumar, Manavalan; Sri Rohita, Duggirala; Elsa, George; Bharathi Sankar, Ammaiyappan; Narasinga Rao, Tata; Karthik, Mani
Abstract : This study demonstrates a facile, cost‐effective, green, and sustainable fabrication of supercapacitor devices using high surface area (2350 m 2  g −1 ) activated carbon fibers as supercapacitor electrode. The electrochemical behavior of the supercapacitor electrodes with different neutral electrolytes such as LiCl, KCl, and NaCl is carefully investigated and compared with natural seawater as an economic and sustainable electrolyte for the first time. The maximum specific capacitance of carbon fibers electrode in different electrolytes is around 101 Fg −1 in LiCl, 134 Fg −1 in KCl, 159 Fg −1 in NaCl, and 172 Fg −1 in natural seawater at a current density of 1 Ag −1 . Surprisingly, the seawater‐based supercapacitor exhibits a very good durability upon 10 000 charge–discharge cycles with 99% of capacitance retention and 99% of coulombic efficiency. For practical validity, integrated solar cell–based supercapacitor pouch cells are investigated. The seawater is explored as an eco‐friendly, cost‐effective, and alternative aqueous electrolyte, which may replace the existing aqueous‐based electrolytes for the fabrication of an economic and green supercapacitor device. Abstract : Conversion of solar energy into electrical energy storage using an integrated solar cell with seawater‐based supercapacitor pouch cells is demonstrated, and the natural seawater is explored as an eco‐friendly and cost‐effective electrolyte for the fabrication of supercapacitor devices.